2012
DOI: 10.3748/wjg.v18.i42.6106
|View full text |Cite
|
Sign up to set email alerts
|

Cost of treating chronic hepatitis B: Comparison of current treatment guidelines

Abstract: The significant cost variations in CHB screening and treatment using different guidelines are relevant for clinicians and policy makers involved in designing population-based disease control programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
0
8
0
2
Order By: Relevance
“…The Gastroenterology Society of Australia recommends that CHB patients with HBV DNA levels > 2000 IU/mL receive treatment regardless of age due to the high risk for HBV-related HCC [25]. Chen CJ et al reported that serum HBV DNA level ≥10,000 copies/mL is a major risk factor for hepatocellular carcinoma irrespective of HBeAg status, ALT level and the presence of cirrhosis [26].…”
Section: Resultsmentioning
confidence: 99%
“…The Gastroenterology Society of Australia recommends that CHB patients with HBV DNA levels > 2000 IU/mL receive treatment regardless of age due to the high risk for HBV-related HCC [25]. Chen CJ et al reported that serum HBV DNA level ≥10,000 copies/mL is a major risk factor for hepatocellular carcinoma irrespective of HBeAg status, ALT level and the presence of cirrhosis [26].…”
Section: Resultsmentioning
confidence: 99%
“…10 The economic modelling showed that the estimated costs attributed to surveillance for chronic hepatitis B (4-30% of the programme's total cost) and HCC screening and surveillance (5-9%) were relatively small. 10 All local general practitioners were invited to free "continuing medical education" seminars on hepatitis B and provided with tailored educational resources. A quarter of the local general practitioners attended at least one seminar in the 18 months following the programme's launch.…”
Section: Local Settingmentioning
confidence: 99%
“…Only 8 to 25% of cases -the exact proportion depending on the guidelines that are followed for treatment initiation -require antiviral treatment. 10 However, in the economic modelling, the cost of antiviral drugs accounted for most (54-76%) of the estimated total cost of the programme. 10 The economic modelling showed that the estimated costs attributed to surveillance for chronic hepatitis B (4-30% of the programme's total cost) and HCC screening and surveillance (5-9%) were relatively small.…”
Section: Local Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Patienten mit Besuchen bei Fachärzten für Infektiologie oder Gastroenterologie erhielten deutlich mehr diagnostische Leistungen und vor allem häufiger eine antivirale Therapie [25]. In einem gesundheitsökonomischen Modell für die Therapie von Hepatitis B-infizierten Patienten errechneten Robotin und Kollegen für Einwanderer aus asiatischen Ländern nach Australien die Kosten für verschiedene leitlinienbezogene Versorgungsansätze (australisches Versorgungsprogramm, AASLD, AESL, APASL) über einen Zeitraum von 50 Jahren [26]. Wegen der unterschiedlichen leitliniengerechten Einschlusskriterien differierten die Kosten zwischen 6344 AUD bei Anwendung der AASLD-Guidelines und 14 039 AUD bei EASL-Guidelines.…”
Section: Diskussionunclassified